2016
DOI: 10.1159/000445035
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Function of PACAP and Its Receptors in the Healthy and Nephrotic Kidney

Abstract: Background/Aims: Plasma deficiency of pituitary adenylate cyclase-activating polypeptide (PACAP) was recently demonstrated in children with nephrotic syndrome (NS). Previous studies have reported an important protective effect of PACAP on kidney proximal tubules. The aim of this study was to explore the expression of PACAP and its receptors PAC1, VPAC1 and VPAC2 in the healthy and nephrotic kidney and to determine if PACAP has an effect on renal proximal tubular cells exposed to albumin. Methods: Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The protein expressions of all PACAP receptors recovered in TAD animals. VPAC1 has already been shown to be expressed in the highest level in proximal tubules (Eneman et al, 2016), and the expression of the PAC1 receptor was demonstrated in the HK-2 cell line (Li et al, 2010). Direct binding of PACAP in kidney diseases has been proven both on PAC1 and VPAC1 receptors (Li M. et al, 2008), suggesting their equal importance in AD-related disorders.…”
Section: Discussionmentioning
confidence: 97%
“…The protein expressions of all PACAP receptors recovered in TAD animals. VPAC1 has already been shown to be expressed in the highest level in proximal tubules (Eneman et al, 2016), and the expression of the PAC1 receptor was demonstrated in the HK-2 cell line (Li et al, 2010). Direct binding of PACAP in kidney diseases has been proven both on PAC1 and VPAC1 receptors (Li M. et al, 2008), suggesting their equal importance in AD-related disorders.…”
Section: Discussionmentioning
confidence: 97%
“…VIPR1 is natively expressed in the kidney 36 , and previous studies have documented endogenous VIPR1 expression in HEK293 cells 31 , 37 , 38 . We first sought to independently verify that endogenous VIPR1 is indeed responsible for the VIP-elicited cAMP elevation measured in our cell model.…”
Section: Resultsmentioning
confidence: 99%
“…There are very few studies addressing the presence and functional role of PACAP in the human kidney. A recent study by Eneman et al [92] found VPAC receptors in normal and nephrotic kidneys and described increased PACAP immunoreactivity in the proximal tubules of nephrotic children, pointing to the reabsorption of filtered PACAP. Another study found decreased PACAP immunoreactivity in tissue samples from renal cancer patients [93].…”
Section: Discussionmentioning
confidence: 99%